Assessment of tear film parameters in females with refractive errors using a single device: an observational study - Alanazi, Mana Alafri; Alanazi, Shahad Abdulrazzaq; Baashen, Mashaaer Abdulwahhab; Almutairi, Meznah Saud; El-Hiti, Gamal Abdel-Rehman (Journal of the Pakistan Medical Association, 2024)
This observational study aimed to evaluate the use of a single portable device to assess the non-invasive tear break-up time (NITBUT), tear meniscus height (TMH), and lipid layer patterns (LLP) in young females with refractive errors (REs). The study was conducted at the College of Applied Medical Science (Female campus), Riyadh, Saudi Arabia between January 5, 2021 to May 15, 2021. Forty young females, with mean age of 23.0± 4.3 years with REs (2.53 ± 2.05 D) and 40 females, mean age 23.8± 4.5 years with healthy eyes were recruited. The tests were administered in the following order: Ocular Surface Disease Index (OSDI), followed by NITBUT, TMH, and LLP. Significant differences (via Mann–Whitney U test) were noted in the median ocular surface disease index (OSDI; p<0.001), NITBUT (p = 0.035), TMH (p = 0.009), and LLP (p<0.001) scores between the study and control groups. ---Continue